Integration of Mediation in Divorce Cases Reviewed from Supreme Court Regulation on Court Mediation Procedures - Junus, Nirwan; Sarson, Mohamad Taufiq Zulfiqar; Elfikri, Nurul Fazri; Muntholib, Job Wahidun (Universitas Negeri Gorontalo, 2024)
The court as a law enforcement instrument has been implementing mediation since 2008. However, the success of mediation is still far from what was expected. This indicates that the integration of mediation in the court system has not been effective, especially related to divorce cases. The integration of mediation into court practice, on the one hand, aims to avoid the accumulation of cases and maximize the function of court institutions in resolving adjudicative disputes, but on the other hand, it increases the judges' workload. Therefore, integrating mediation into court proceedings can be an instrument in reducing the divorce rate. This research uses an empirical normative approach in terms of Supreme Court Regulation Number 1 of 2016. The obtained data will be analyzed qualitatively. The research results indicate that the integration of mediation in divorce cases at the Gorontalo City and Regency Religious Courts has prioritized societal values, particularly deliberation to reach the best solution for the parties involved. However, this approach does not seem to align well with the social dynamics in Gorontalo City. This is because there are still several key factors that hinder achieving the best results through mediation. The failure to reach critical points in these deliberations results in a minimal success rate for mediation in resolving divorce cases, as evidenced by the relatively high number of divorce decisions. This is often due to the parties involved blaming each other and being unwilling to negotiate for a mutual agreement.